Cases on Internationalization Challenges for SMEs - Moreira, António Carrizo (IGI Global, 2021)
With the globalization process, firms are seeking to expand their activities to international markets but are also ""feeling"" expanded competition from abroad. Small and medium-sized enterprises (SMEs), though seeking to expand abroad, have particularities that hinder their natural international expansion path due to particular barriers and challenges that most multinational firms have already overcome. Cases on Internationalization Challenges for SMEs provides a set of case studies on the internationalization of SMEs in order to share the latest empirical research findings in the field of in.